The role of Internal Audit Standards IIA`s in improving the local guideline and its reflection on the efficiency of internal audit performance - ابراهيم, محمد عبد الله; حسين, حسن فائز (Journal of Economics and Administrative Sciences, 2025)
The function of internal auditing has become an important function that aims at achieving objectives that are compatible with these developments and changes that have occurred in many countries in the world, which required the emergence of professional associations and institutes in the profession of internal auditing. Improve the guideline of the internal audit units issued by the Federal Audit Bureau to enhance the efficiency of internal audit performance in Iraqi government units. The researchers adopted the statistical method of proving the hypothesis by constructing a questionnaire that included three main axes: supporting the senior management in adopting the current guide, and the second being the importance of improving the guide according to the IIA standards. The third and final axis is dedicated to enhance the efficiency of internal audit units by improving the guideline In accordance with the IIA standards. A total of 114 questionnaires were distributed on the sample and 99 were retrieved. The good for the analysis was 92 and the analytical descriptive method was adopted by analyzing the results of the questionnaire and linking them to the results of the data collection and analysis. Statistical and hypothesis testing through the use of the statistical package for social sciences SPSS, and one of the most important results reached is that the internal audit units sample the study is committed to apply the guide guide in its work, but this guide is not enough to enhance the efficiency of internal audit units, and this commitment is reflected on The role and importance of internal audit at present. As the research reached a set of conclusions, the most important is the improvement of the guide to internal audit units according to the IIA standards to reflect on the efficiency of the performance of internal audit units.